Hydrocortisone decreases apoptosis in jejunum of horses subjected to experimental ischemia and reperfusion - Alves, Geraldo Eleno S.; Mendes, Heloisa M.F.; Alves, Tiago G.S.; Faleiros, Rafael R.; Vasconcelos, Anilton C.; Santos, Renato L.; Rio Tinto, Jorge J.M. (Pesquisa Veterinária Brasileira, 2011)
In order to evaluate the effect of hydrocortisone on apoptosis in the jejunum of horses subjected to ischemia and reperfusion, ten horses were paired and grouped into two groups - treated (n=5) and non treated (n=5). Segments of the jejunum were used as controls (C), or as venous ischemia (VIsc), which were subjected to 2h of ischemia followed by 2 or 12h of reperfusion. C samples were collected at time zero (prior to ischemia) and VIsc samples were collected at 2h of ischemia and at 2 and 12h of reperfusion. TUNEL positive apoptotic cells were counted in 10 microscopical fields in deep mucosa from each horse throughout the time course. After 12h of reperfusion, the number of apoptotic cells in treated group were significantly lower than in untreated animals, indicating that hydrocortisone inhibits apoptosis. These results indicate that hydrocortisone has a beneficial effects favoring the maintenance of jejunal integrity in horses with ischemia and reperfusion injuries by preventing apoptotic cell death. Com o objetivo de avaliar o efeito da hidrocortisona sobre a apoptose no jejuno de equinos submetidos à is-quemia e reperfusão, dez cavalos foram agrupados em dois grupos: tratado (n=5) e não-tratado (n=5). Foi utilizado um segmento do jejuno como controle (C) e outro foi submetido a isquemia venosa (VIsc) por 2h seguida de 2 ou 12 h de re-perfusão. Amostras de C foram coletadas no tempo zero (antes da isquemia) e amostras de VIsc foram coletadas após 2h de isquemia e a 2 e 12h de reperfusão. Células apoptóticas TUNEL positivas foram contadas em 10 campos microscópicos da mucosa na região das criptas de cada animal em cada tempo. Após 12h de reperfusão, o número de células apoptóticas no grupo tratado foram significativamente menores do que no grupo não-tratado, indicando que a hidrocortiso-na inibe a apoptose. Esses resultados mostram que a hidro-cortisona tem efeito benéfico favorecendo a manutenção da integridade do jejuno em cavalos com lesão de isquemia e reperfusão por prevenir a morte celular por apoptose.